2014
DOI: 10.1016/j.clinthera.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrochlorothiazide on the Pharmacokinetics, Pharmacodynamics, and Tolerability of Canagliflozin, a Sodium Glucose Co-transporter 2 Inhibitor, in Healthy Participants

Abstract: Adding canagliflozin treatment to healthy participants on HCTZ treatment had no notable pharmacokinetic or pharmacodynamic effects; canagliflozin coadministered with HCTZ was generally well tolerated, with no unexpected tolerability concerns. ClinicalTrials.gov identifier: NCT01294631.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…A recent crossover study on canagliflozin and hydrochlorothiazide found adverse events of mild severity including orthostatic hypotension. 5 Other drugs commonly used in patients with type 2 diabetes may potentiate problems. The common concomitant use of statins and thiazide diuretics in patients with type 2 diabetes taken to reduce the risk of vascular events may further complicate the problems with SGLT2 inhibitors as they may decrease insulin secretion; however, the use of angiotensin converting enzyme inhibitors may increase insulin secretion.…”
mentioning
confidence: 99%
“…A recent crossover study on canagliflozin and hydrochlorothiazide found adverse events of mild severity including orthostatic hypotension. 5 Other drugs commonly used in patients with type 2 diabetes may potentiate problems. The common concomitant use of statins and thiazide diuretics in patients with type 2 diabetes taken to reduce the risk of vascular events may further complicate the problems with SGLT2 inhibitors as they may decrease insulin secretion; however, the use of angiotensin converting enzyme inhibitors may increase insulin secretion.…”
mentioning
confidence: 99%
“…In previous reported studies, both positive and negative ionization were adapted for analyzing canagliflozin in biological samples; ammonium adduct ions [M + NH 4 ] + (m/z = 462.1) in positive ionization were adapted for the determination of canagliflozin levels in plasma in clinical trials using an API 4000 equipped with turbo ion spray interface (AB Sciex, Framingham, MA, USA; Devineni et al, 2013Devineni et al, , 2014Devineni et al, , 2015Inagaki et al, 2014;Murphy et al, 2015). Single abundant product ions [M-H] -(m/ z = 443.0) in negative ionization were adapted for analyzing canagliflozin in rat plasma using the ACQUITY TM UPLC system coupled to a triple-quadruple tandem mass spectrometer (Micromass Quattro micro TM Waters Corp., Milford, MA,USA; Iqbal et al, 2015).…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Under limited conditions, LC-MS/MS methods are preferred and required for the analysis of various compounds in basic and clinical research. In fact, the concentration of canagliflozin in the plasma of patients in clinical trials was determined by the LC-MS/MS method (Devineni et al, 2013(Devineni et al, , 2014Inagaki et al, 2014;Murphy et al, 2015); however, the parameters of the assay were not fully disclosed in these papers. In order to overcome such shortcomings, a highly sensitive LC-MS/MS method for the quantitative analysis of canagliflozin in a lower volume of rat plasma (0.1 mL) was developed and applied to a pharmacokinetic study in rats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations